Perbedaan Kandungan Asam Askorbat Buah Nanas dan Keripik Nanas yang Beredar di Pasar Wonokusumo Menggunakan Metode Spektrofotometri Ultra Violet - Dinda Alya Hasan; M.A. Hanny Ferry Fernanda (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Vitamin C is one of the vitamins needed by the body that acts as an antioxidant to form a defense against free radicals. One of the fruits that contain vitamin C is pineapple. Pineapple is one of the most popular types of fruit. One of the most popular processed pineapple fruit is pineapple chips. This study aimed to determine the differences in the content of vitamin C in pineapple fruit and chips. The analytical method used to determine vitamin C levels is UV-Vis Spectrophotometry because this method is quite accurate and more efficient and produces high accuracy and precision. The results of this study are the linearity test obtained a linear regression equation, namely y = 0.0363x + 0.0687 with a value of R² = 0.993. Successively obtained the average level of pineapple fruit is 0.191 %w/w, brand A pineapple chip is 0.099 %w/w, and pineapple chips brand B is 0.111 %w/w. Based on the results of statistical tests, it is known that there are differences in vitamin C levels in pineapple and pineapple chips.